Determinants of functionality of community health committees: A case of Mombasa County, Kenya - Patta, Shem Onyango; Oluoch, Musa; Osuga, Ben Onyango (International Journal of Professional Practice, 2021)
The achievement of better health outcomes is generally believed to be possible to secure through the development and support accorded to health systems. Community Health Committees comprised of selected community membership focused on coordinating activities regarding the health of the community on behalf of their community, have been identified as a useful health governance structure and offer oversight and leadership in the execution of services related to the community’s health. It is heavily opined that increasing the space of decision making within lower health systems levels, and the involvement of the citizens in priority setting enhances health systems responsiveness. In spite of the likely effects, the participation of the community is surrounded with challenges as suggestion of studies point that committees of health within African countries are not optimally functioning. The main objective of this study was to assess the factors influencing the functionality of Community Health Committees. Specific Objectives were: to examine the role of communication, committee composition, training and support supervision. The study adopted a descriptive cross-sectional research study design to interview 162 respondents in selected Community Health Units. Stratified random sampling was used to identify the respondents. The research instrument used in the study was a questionnaire, additionally Key Informant Interviews were administered to six health workers within the six sub-counties to understand their perception, understanding and knowledge of functionality of community health committees. Descriptive and inferential statistics were used to summarize the data. The findings established that communication, composition, training and support supervision had positive and significant influence on functionality of Community Health Committee. The study concluded that community health committees where there was effective communication, proper composition, had undergone effective trainings and were properly supervised had better functionality and improved governance